AKTIVITAS MATEMATIKA DALAM PERMAINAN TRADISIONAL GATRIK - Samnur Saputra (Universitas Islam Nusantara, 2016)
Mathematics is a subject learned from pre-school to college. Nevertheless, many students consider mathematics difficult andboring. In reality mathematics is often found in everyday life. Even in culture even though learning mathematics is tucked away.The culture that is most familiar among students is the traditional game. One of these traditional games is “Gatric”. Playinggatrik means students have learned some activities in mathematics. The purpose of writing this paper is to show the mathematicalactivities that exist in the Gatric game. Gatrik is a traditional game that involves two players or more who use two pieces ofwood / wood that have different lengths. This paper is based on a literature review from some supporting literature. Literatureused as a supporting source is the result of research.